Toleration and Persecution in England, 1660–89 - Mullett, Charles F. (Church history, 1949)
During the years of their greatest tribulation, English Protestant dissenters were steadily buoyed up by numerous efforts in their behalf; stemming from various sources, these efforts were inspired by motives equally various. Gestures toward a peaceful settlement actually began before Charles II ascended the throne. Little persecution marked the Cromwellian regime and although the Establishment had possessed a Presbyterian tinge, organized Presbyterianism had made little headway. The Church was rather an assemblage of congregations than a compact hierarchy. While Episcopalians had been forced from their livings, many did not appear vindictive, and as the Restoration approached, a tolerant mood seemed uppermost.